The mechanical performance of glass fibre reinforced composite based sandwich structure - Xiaoli Zhu (Functional Materials, 2018)
In this study, a sandwich structure of composite material based on glass fiber was proposed. Its bending properties were investigated, the strength and thermal properties of the sandwich structure and the materials of its components were tested. The results showed that the maximum bending load of the sandwich was 250 N, 500 N and 1000 N, respectively, when the density of the core material was 50 kg/m³, 75 kg/m³ and 100 kg/m³. The temperature had a slight effect on the tensile property of the PU core material, the ultimate tensile load of the sandwich, whose core material density was 100 kg/m3, was 106 N, 98 N, 93 N and 61 N, respectively, when the temperature was 20 °C, 40 °C , 60 °C and 80 °C. The peak value of the rate of energy release of the deformation of the sandwich interface increased with increasing temperature, and the peak value occurred when the crack shifted 40 ~ 50 mm. At temperatures above 80 °C, the resin used in adhesion of the surface evolved from a glassy state to a highly elastic state.